2016
DOI: 10.1016/j.healun.2016.01.1222
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender differences and factors related to change in health-related quality of life from before to 6 months after left ventricular assist device implantation: Findings from Interagency Registry for Mechanically Assisted Circulatory Support

Abstract: Background Gaps in the literature exist regarding health-related quality of life (HRQOL) early after left ventricular assist device (LVAD) surgery. The purposes of our study were to describe HRQOL over time, by age and gender, and identify risk factors for poor HRQOL early after LVAD implant. Methods Patients (n=7,353) from INTERMACS received a continuous flow LVAD as a primary implant at 133 U.S. hospitals. Of these, 5,640 patients had pre LVAD HRQOL data, and 3,353 patients had 6 month post LVAD HRQOL data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 42 publications
6
60
0
Order By: Relevance
“…The first strategy represents a moderate decrease in scores, while the last strategy represents the “worst case” scenario and provides a lower bound for the distribution of true HRQOL scores. The last strategy was used in previous HRQOL reports from Intermacs 810 based on the spread of VAS scores (<10) for Intermacs Profile 1 patients, so we wanted to test the veracity of this approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first strategy represents a moderate decrease in scores, while the last strategy represents the “worst case” scenario and provides a lower bound for the distribution of true HRQOL scores. The last strategy was used in previous HRQOL reports from Intermacs 810 based on the spread of VAS scores (<10) for Intermacs Profile 1 patients, so we wanted to test the veracity of this approach.…”
Section: Methodsmentioning
confidence: 99%
“…7 PROs are an integral component of the Intermacs registry, which has previously reported improved HRQOL across time. 810 These findings provide important information on outcomes for clinicians to share with advanced heart failure patients considering treatment options, including implantation of left ventricular assist devices (LVADs). However, changes in HRQOL from before to after implant have been related to pre-implant heart failure severity, co-morbidities, implant strategy, and post-implant adverse events, and the optimal approach to handling missing HRQOL data when patients are often missing these assessments due to the severity of their illness requires further elucidation.…”
mentioning
confidence: 99%
“…Previous studies have shown that ventricular assist devices improve QoL in older and younger patients from before to six months after LVAD implantation, and older patients report more problems with mobility early after implant than younger patients. [12] In this study, the mean age of the German population was higher than the Turkish population. The German group had significantly lower scores on the KCCQ subscales of physical limitation and symptom frequency, consistent with the literature.…”
Section: Discussionmentioning
confidence: 48%
“…Finally, Grady et al examined the impact of age (n=493 > 70 years, n=977 < 70 years) among patients enrolled in INTERMACS and found that despite a higher selfreported QOL prior to LVAD implant compared to younger cohorts, older adults demonstrated equivalent gains in QOL metrics 1 year after implantation. 37 While lower QOL score and rehospitalization after LVAD were important variables in subsequent QOL scores, age did not influence this metric.…”
Section: Left Ventricular Assist Device Therapymentioning
confidence: 87%